Central Regulation of Metabolism by Protein Tyrosine Phosphatases - Tsou, Ryan; Bence, Kendra (Frontiers in Neuroscience, 2013)
Protein tyrosine phosphatases (PTPs) are important regulators of intracellular signaling pathways via the dephosphorylation of phosphotyrosyl residues on various receptor and non-receptor substrates. The phosphorylation state of central nervous system (CNS) signaling components underlies the molecular mechanisms of a variety of physiological functions including the control of energy balance and glucose homeostasis. In this review, we summarize the current evidence implicating PTPs as central regulators of metabolism, specifically highlighting their interactions with the neuronal leptin and insulin signaling pathways. We discuss the role of a number of PTPs (PTP1B, SHP2, TCPTP, RPTPe, and PTEN), reviewing the findings from genetic mouse models and in vitro studies which highlight these phosphatases as key central regulators of energy homeostasis.